الدرس اللهجي في كتاب "المزهر في علوم اللغة وأنواعها" للسيوطي : دراسة وصفية استقرائية تحليلية - معمري، حميد بن مهنا بن سليم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study sheds light on the ancient Arabic dialects in AlMezher's book on language sciences and its types by Suyuti, which is rich of many of them. The Arabic dialects were followed, extracted and then distributed to the levels of the linguistic pyramid starting from its base which is represented by the vocal level, that had the largest share of linguistic phenomena especially if we know that the operative side was affected more quickly than others, followed by morphological and grammatical levels and finally the semantic level. The most important objectives of this study that we endeavored to achieve them, were to show the definitions of the terms dialect and language, their differences and connections , and the factors behind creating these dialectics and their link to the common Arabic, in addition to looking to all the Arabic dialects mentioned in the book Al-Mizhar Al-Souti and showing its relation to Arabic language and their influences. In this study, we found that the term "dialect" was not well known in the case of linguists who used "Language" instead. Moreover, the study reveals that the book of Al-Mizhar by al-Suyuti is rich of many ancient Arabic dialects like the dialect of the people of Hijaz and the dialect of the two great camps. In addition, the study concluded confidently that the Arabic language was affected by Arabic dialects by taking the best form tbem while Arabic language had great influence on Arabic dialects by refining themfrom linguistic defects that were used in Arab forums such as literary markets, trade or during the pilgrimage